Association of early Post-Operative Outcomes with Metabolic Syndrome after Coronary Artery Bypass Grafting - Ghulam Kibriya, Amna Abbas, Hina Aftab, Muhammad Athif Akram, Yahya Saeed, Omar Iqbal, Azhar Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study is to find out the association of metabolic syndromewith early outcomesafter CABG. Study Design: This was a comparative study. Place and Duration: This study was performed from the first of July 2020 to the first of January 2021 at the Cardiac Surgery Department, PIC, Jail Road, Lahore Methodology: The approach of non-probability sampling was applied. After obtaining consent on a consent form, 172 Patients (86 in the exposed group and 86 in the non-exposed group) were included. Results: The average age of the participants in this study was 55.30 ± 8.77 years; there were 130 cases (75.6%) of men and 42 cases (24.4%) of women. There were 56 (65.12%) men and 30 (34.88%) women in the exposed group, compared to 74 (86.05%) men and 12 (13.95%) women in the non-exposed group. There were 5(5.8%) cases in the exposed and 1(1.2%) case in the non-exposed group of post-operative stroke found with a p-value of 0.096. Postoperative pneumonia occurred in 9(10.2%) of the exposed and 2(2.3%) of the non-exposed group (p-value 0.05). Mortality was found in 11 (12.8%) patients in the exposed and 6 (7%) in the non-exposed group (p-value = 0.20). Conclusion: Because many MetS syndrome factors are under our control, it is important to prevent it early especially in cases of CABG, to get better outcomes. Post-operative pneumonia was significantly greater in the exposed groups, with a p-value of 0.05, while stroke and mortality were found statistically insignificant, with a p-value of >0.05, the current study's findings were quite different and unexpected. It is suggested that larger-scale studies be conducted. Keywords: CABG, Lipid Profile, Diabetes, Obesity, Mortality